口腔顔面指趾症候群I型の1症例 - 迫田, 隅男; 鹿嶋, 光司; 吉田, 真穂; 井川, 加織; 市來, 剛 (日本口腔外科学会雑誌, 2010)
Oral-facial-digital syndrome is a rare morphologic anomaly with a genetic origin. We report a case of oral-facial-digital syndrome I. The patient was a 1-month-old girl who had a tumor on the tongue, a lobulated tongue, hyperplasia of the cheek frenulum, and a high palate. Functional disorders such as dysphagia were not present. The tumor on the tongue, lobulated tongue, and hyperplastic frenulum of the cheek were treated. There were no complications of the surgical wound after operation. She was followed up at the departments of pediatrics and oral surgery. At the age of 5 years 6 months, her intellectual development was the lower limit of normal, and dysarthria was observed. This syndrome has a good prognosis unless abnormalities develop in the central nervous system. However, our patient requires careful observation because she has a history of the agenesis of the corpus callosum caused by the multiple cysts in the central nervous system.